PI3K/AKT/mTOR Pathway in Ovarian Cancer Treatment: Are We on the Right Track? - Gasparri, Maria Luisa; Bardhi, Erlisa; Ruscito, Ilary; Papadia, Andrea; Farooqi, Ammad Ahmad; Marchetti, Claudia; Bogani, Giorgio; Ceccacci, Irene; Mueller, Michael D.; Benedetti Panici, Pierluigi (Geburtshilfe und Frauenheilkunde, 2017)
The high recurrence rate and the low overall survival in ovarian cancer suggest that a more specific therapeutic approach in addition to conventional treatment is required. Translational and clinical research is investigating new molecular targets in order to find an alternative way to affect tumor growth and to minimize the overlap of toxicity of antiblastic agents. Given its implication in many cellular activities including regulation of cell growth, motility, survival, proliferation, protein synthesis, autophagy, transcription, as well as angiogenesis, PI3K/AKT/mTOR is one of the most investigated intracellular signaling pathways. A dis-regulation of this pathway has been shown in several tumors, including ovarian cancer. In this setting, mTor proteins represent a potential target for inhibitors, which could ultimately play a pivotal role in counteracting cellular proliferation. Recently, mTor inhibitors have been approved in the treatment of pancreatic neuroendocrine tumors, mantle cell lymphoma and renal cancer. Clinical trials have assessed the safety of these drugs in ovarian cancer patients. Ongoing phase I and II studies are evaluating the oncologic outcome of mTor inhibitor treatment and its effect in combination with conventional chemotherapy and target agents.
Keywords: everolimus; mTOR inhibitors; ovarian cancer; target therapy; temsirolimus; PI3K/AKT/mTOR